Application of Problem Base Learning Model Based on Critical Thinking Concepts in Improving Students’ Learning Outcomes at SMP Negeri 3 Menggala - Baniyah, Baniyah; Subandi, Subandi; Jaenullah, Jaenullah (CV. Creative Tugu Pena, 2024)
This research is qualitative research with a case study type. The research subjects were conducted purposively. Meanwhile, the data collection techniques used are observation, interviews and documentation. The data analysis used is the Miles and Huberman model. This research found that: (1) Learning planning uses a problem based learning model based on the concept of critical thinking, namely by compiling a syllabus, lesson plans, and analyzing basic competencies, materials, activities and time allocation. Learning materials come from LKS and government PAI textbooks, delivered using a problem-based approach, according to the time allocation in the syllabus, and by utilizing learning media. Documents such as syllabus, lesson plans, modules and learning tools are obtained from the district level MGMP work program, and there is a lesson plan preparation workshop at the beginning of each semester. (2) Implementation of learning at SMP Negeri 3 Menggala For Class Viii Students involves steps such as creating a pleasant learning atmosphere, orientation towards problems, defining problems, and developing and presenting work. Teachers help students organize learning tasks, guide investigations, and design reflection and assessment activities. Teachers overcome obstacles by providing motivation, patience, and repetition. (3) Evaluation of learning at SMP Negeri 3 Menggala includes PTS, PAS, and final learning through written, oral and practical tests. Evaluation serves as a correction tool for teacher deficiencies and allows improvements in subsequent meetings, as well as identifying student obstacles during learning. Keywords: Critical Thinking Concepts, Learning Outcome